Herman Gorter: Poems of 1890 A Selection - Gorter, Herman (UCL Press, 2015)
Commonly viewed as a revolutionary and propagandist Herman Gorter (1864-1927) is often overlooked despite his lasting contribution to Dutch poetry. This selection of thirty-one poems, translated by Paul Vincent, focuses on Gorter's experimental love and nature lyrics in Poems of 1890, and the Introduction sets the poems in the context of his earlier seminal work 'Mei' (May) as well as his often neglected Socialist verse. The lyrical expansiveness, consistent use of rhyme and vivid imagery of the Dutch landscape that characterises 'Mei' evolves into more fragmentary verse in Poems of 1890, and the joyful celebratory tone of Gorter's poetry increasingly co-exists with a sense of isolation and introspection. This can be viewed in the context of a rapidly changing political scene in Europe in the prelude to the First World War and the Russian Revolution. This is a valuable collection that revisits Gorter's literary and political legacy, and introduces English-speaking readers to a selection of his most accessible and lyrical poems. Praise for Herman Gorter: Poems of 1890 'In his introduction, Paul Vincent notes that in May only fragments have been translated into English and then apparently reveals the loose wrist, his translation of the first twelve lines, as steep and sound as Gorter's text, and as beautiful as The 1890 poems in this bundle: 'A newborn springtime and a newborn sound ...' (p. 3). That tastes like more.' Filter 'A free e-book of Herman Gorter's Poems of 1890: A Selection (UCL Press) is a rare gift to the English-reading world. Translating highly lyrical poetry is probably the most challenging thing for a translator, but time and again Paul Vincent succeeds in suggesting something of the genius of the most important Dutch lyrical poet.' Times Higher Education